how would you factor: 6x^2-x-2 x^2-3x+2x-6 81y^2-36 11/12/2013 | Samuel from South Point, OH | 2 Answers | 0 Votes Mark favorite Subscribe Comment
6x^2-x-2 = (3x-2)(2x+1), inverse foil x^2-3x+2x-6 = x(x-3) + 2(x-3) = (x+2)(x-3), by grouping 81y^2-36 = (9y+6)(9y-6), using the difference of two squares formula 11/12/2013 | Robert J. Comment Comments awesome thank you very much. Also how would i factor 9x^2-36 x^2-11x+24. which ones are Quad Equations factor by grouping product sum (x-12)(x-2) 9(x-2)(x+12) (x-4)(x+4) 11/12/2013 | Samuel from South Point, OH Comment
awesome thank you very much. Also how would i factor 9x^2-36 x^2-11x+24. which ones are Quad Equations factor by grouping product sum (x-12)(x-2) 9(x-2)(x+12) (x-4)(x+4) 11/12/2013 | Samuel from South Point, OH
a^{2} -b^{2} = (a - b)(a + b) ~~~~~~~~~~ 81x^{2} - 36 = 9(9x^{2} - 4) = 9(3x - 2)(3x + 2) 11/12/2013 | Nataliya D. Comment
Comments